Islam, Gender and Self: Rethinking Transnational Belonging and Intersectional Experiences of Tamil Muslim Women in Singapore. Issue 1 (June 2021) - Menon, Pavithra Nandanan
Much has been written about Tamil diaspora as well as Muslim women in Singapore, but only separately. This exploratory article would aim to fill that empirical gap by focusing on a detailed ethnographic study of Tamil Muslim women in Singapore as gendered racialized bodies, thus examining the actualities and dilemmas of being visibly transnational Muslim women in a diasporic space by unpacking the interconnections between identity and belongingness. This work uses a trans-local lens to understand the transnational experiences and hybridized shape-shifting identities of Tamil Muslim women in a diasporic space like Singapore, thus reconceptualizing transnationalism and diaspora. Using an intersectional lens also gives a new edge in addressing the multiple loopholes and interconnections that come together to impact the everyday experiences of Tamil Muslim women in Singapore. This research would thus contribute to feminist literature and (Tamil diaspora) diaspora literature by exploring intersections of identities such as race, religion, and gender that interplay in relation to transnational belongingness from a female standpoint, that of the Tamil Muslim women in Singapore based on the everyday experiences and realities of the social structure within their local environment.